Precision Electroweak Physics at Electron-Positron Colliders - Roth, Stefan (Springer Tracts in Modern Physics, 2007)
This up-to-date volume reviews the recent contributions of electron-positron colliders to the precision test of the electroweak Standard Model. In particular, it contains a short summary of the measurements at the Z resonance and gives an overview of the electroweak processes above the Z. Subsequently, the measurement of the W mass at LEP is discussed in detail. The implications for the precision test of the Standard Model are presented, giving the status of the global electroweak fit before the startup of Large Hadron Collider. The final chapters give an outlook on the electroweak physics at a future linear collider. The book also features many illustrations and tables. Readers obtain a coherent overview of the results of 20 years of electroweak physics conducted at electron-positron colliders.